The need for an integrated approach for chronic disease research and care in Africa. (29th November 2016) - Barr, A. L.; Young, E. H.; Smeeth, L.; Newton, R.; Seeley, J.; Ripullone, K.; Hird, T. R.; Thornton, J. R. M.; Nyirenda, M. J.; Kapiga, S.; Adebamowo, C. A.; Amoah, A. G.; et al.
Abstract : With the changing distribution of infectious diseases, and an increase in the burden of non-communicable diseases, low- and middle-income countries, including those in Africa, will need to expand their health care capacities to effectively respond to these epidemiological transitions. The interrelated risk factors for chronic infectious and non-communicable diseases and the need for long-term disease management, argue for combined strategies to understand their underlying causes and to design strategies for effective prevention and long-term care. Through multidisciplinary research and implementation partnerships, we advocate an integrated approach for research and healthcare for chronic diseases in Africa.